Thermoplastic composite from Keruing Belimbing (effects of particle size and filler content) / Mohd Hafiz Ahmad - Ahmad, Mohd Hafiz (2004)
This study was conducted to determine the suitability of Keruing Belimbing as filler in the making process of thermoplastic composite and to determine its physical and mechanical properties. The sawdust and Polypropylene (PP) were blended in a Dispersion Mixer Machine and then molded into a composite in a mould. Based on the results, it was found that the higher percentage of filler content that we used, the value of strength properties is decrease. The strength properties of thermoplastic also increase with the size of particle that we used. Water absorption also increase when filler content increase. We concluded that Keruing Belimbing sawdust is suitable to be as filler in the making process of thermoplastic composite.